Проектирование энергосберегающих асинхронных двигателей с использованием модифицированного критерия приведенных затрат - Петрушин, Виктор Сергеевич (НТУ "ХПИ", 2014)
Предлагается модификация критерия приведенных затрат за счет использования коэффициентов значимости эксплуатации и приоритета учета активных потерь, что позволяет согласовать максимум КПД и минимум приведенных затрат. Проведен анализ влияния коэффициента инфляции на критерий приведенных затрат.

The paper introduces a modified criterion of reduced costs that employs coefficients of operation significance and priority of ohmic loss accounting to allow matching maximum efficiency with minimum reduced costs. Impact of the inflation factor on the criterion of reduced costs is analyzed.
Energy-efficient induction motors designing with application of a modified criterion of reduced costs
Keywords: КПД; коэффициент инфляции; энергоресурсы; induction motor; optimization design; modification; rate of inflation